Flue‐cured tobacco response to sublethal rates of glufosinate. Issue 1 (19th January 2022) - Vann, Matthew; Johnson, Virginia Alice; Jordan, David; Fisher, Loren; Edmisten, Keith
Abstract: Glufosinate is a broad‐spectrum, contact herbicide that is currently applied to genetically engineered row crops that tolerate exposure to the compound. Flue‐cured tobacco ( Nicotiana tabacum L.) is susceptible to glufosinate, yet it is commonly grown in close proximity to tolerant crops in North Carolina. The impact of glufosinate drift on flue‐cured tobacco is not known. Research was conducted in North Carolina to test the effects of sublethal rates of glufosinate (0.270, 0.135, 0.067, 0.034, 0.017 lb a.i. acre –1 ) on flue‐cured tobacco injury, yield, visual quality, financial value, and leaf chemistry. Simulated drift was imposed approximately 5 wk after transplanting. Visual injury increased with exposure rate and ranged from 15 to 83% and from 10 to 83% 1 and 2 wk after treatment, respectively. Cured leaf yield was reduced by 45% at the highest sublethal exposure rate and exhibited a linear decline of 47 lb acre –1 for every 0.01 lb glufosinate acre –1 . Visual quality and per acre financial value were not affected by glufosinate, most likely due to the loss of necrotic tissue and late‐season plant growth compensation. Residues of glufosinate in green and cured leaves were likewise not detected. Producers and commercial applicators should exercise caution when applying glufosinate around flue‐cured tobacco because of the injury and yield loss that can result from physical spray drift, as well as the inability to sell tobacco that has been exposed to a pesticide that is not labeled for application. Core Ideas: Drift of nonlabelled herbicides can injure tobacco and result in contract losses. Glufosinate injury may range from ≈10 to >80% over the 14‐d period after exposure. Cured leaf yield may decline by 3–45%, depending upon the exposure rate.